REPRESENTASI KESENJANGAN KELAS SOSIAL TERHADAP TOKOH UTAMA DALAM NOVEL HELLO KARYA TERE LIYE: KAJIAN MARXISME - Ilma Nurfaizil; Elsa Mulya Karlina (CV. Adiba Aisha Amira, 2025)
This research aims to show the representation of social class inequality experienced by the main character in the novel hello by Tere Liye through a literary sociology approach with Marxist studies. The main focus of this research is to answer how the social class inequality faced by the main character is depicted in the novel. The second focus is to answer how the impact of social class inequality faced by the main character is depicted in the novel. This research uses a qualitative descriptive method with library study techniques and indepth reading. Data obtained from text quotations, narration and dialogue in the novel Hello by Tere Liye were then analyzed using Karl Marx’s social class theory. Especially the concept of bourgeoisie (upper class), proletary (lower class), class exploitation and alienation. The research result show that the social class gap in the novel Hello by Tere Liye is represented through economic differences, access to education and health services between the characters Hesty (upper class) and Togpr (lower class). From the gap between the two classes, impacts arise such as class exploitation experienced by the lower class and social alienation experienced by the two classes. This research shows social criticism of injustice and class domination in society, which is reflected in the relationships between characters and the novel’s narrative.